Management considerations of massive hemoptysis while on extracorporeal membrane oxygenation. (November 2016) - Pitcher, Harrison T; Harrison, Meredith A; Shaw, Colette; Cowan, Scott W; Hirose, Hitoshi; Cavarocchi, Nicholas
Background: Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is a life-saving procedure in patients with both respiratory and cardiac failure. Bleeding complications are common since patients must be maintained on anticoagulation. Massive hemoptysis is a rare complication of ECMO; however, it may result in death if not managed thoughtfully and expeditiously. Methods: A retrospective chart review was performed of consecutive ECMO patients from 7/2010-8/2014 to identify episodes of massive hemoptysis. The management of and the outcomes in these patients were studied. Massive hemoptysis was defined as an inability to control bleeding (>300 mL/day) from the endotracheal tube with conventional maneuvers, such as bronchoscopy with cold saline lavage, diluted epinephrine lavage and selective lung isolation. All of these episodes necessitated disconnecting the ventilator tubing and clamping the endotracheal tube, causing full airway tamponade. Results: During the period of review, we identified 118 patients on ECMO and 3 (2.5%) patients had the complication of massive hemoptysis. One case was directly related to pulmonary catheter migration and the other two were spontaneous bleeding events that were propagated by antiplatelet agents. All three patients underwent bronchial artery embolization in the interventional radiology suite. Anticoagulation was held during the period of massive hemoptysis without any embolic complications. There was no recurrent bleed after appropriate intervention. All three patients were successfully separated from ECMO. Conclusions: Bleeding complications remain a major issue in patients on ECMO. Disconnection of the ventilator and clamping the endotracheal tube with full respiratory and cardiac support by V-A ECMO is safe. Early involvement of interventional radiology to embolize any potential sources of the bleed can prevent re-hemoptysis and enable continued cardiac and respiratory recovery.